Answer:
The answer is x=5
A lotㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤ
Answer:
False
Step-by-step explanation:
SA of cone = pi×r×l + pi×r²
= pi×r×(3r) + pi×r²
= 3pi×r² + pi×r²
= 4pi×r²
SA of cylinder = 2pi×r×h + 2pi×r²
= 2pi×r×2r + 2pi×r²
= 4pi×r² + 2pi×r²
= 6pi×r²
Answer:
.
Step-by-step explanation:
Answer:
-8x² + 28x - 20
Step-by-step explanation:
To simplify the expression A(x) = ( 2x - 5 )( x + 1 ) - ( 5x - 3 )( 2x - 5 ), you can start by using the distributive propertyto expand both sets of parentheses and then combine like terms:
A ( x ) = ( 2x - 5 ) ( x + 1 ) - ( 5x - 3 ) ( 2x - 5 )
( 2x - 5 ) ( x + 1 )
2x ( x ) + 2x ( 1 ) - 5 ( x ) - 5 ( 1 )
2x² + 2x - 5x - 5
( 5x - 3 ) ( 2x - 5 )
5x ( 2x ) + 5x ( -5 ) - 3 ( 2x ) - 3 ( -5 )
10x² - 25x - 6x + 15
2x² + 2x - 5x - 5 - ( 10x² - 25x - 6x + 15)
2x² + 2x - 5x - 5 - 10x² + 25x + 6x - 15
( 2x² - 10x² ) + ( 2x - 5x + 25x + 6x ) + ( -5 - 15 )
-8x² + 28x - 20
∴ A ( x ) = -8x² + 28x - 20